Dynamics of the large-scale tropospheric circulation During summer monsoon and tropical droughts - AWADE, S. T.; TOTAGI, M. Y.; BAWISKAR, S. M.; SIKKA, D. R. (MAUSAM, 1984)
Fourier analysis has been used for monthly mean geopotential height for 700 mb and 300 mb levels for the months April through August for the years 1967, 1972, 1973, 1974 and 1977. The years 1967, 1973, 1977 are good monsoon years and 1972, 1974 are drought years. From the Fourier coefficients the transport of momentum and of sensible heat, wave to wave and wave to zonal interactions have been computed in wave number domain. Waves 1 to 3 show contrasting features in years of good and bad monsoons. Northward transport of momentum across subtropical latitudes is large in good monsoon years while northward transport of sensible heat is large in bad monsoon years. In drought years there is large divergence of flux of sensible heat in subtropics, while there is large divergence of momentum in good monsoon years. In good monsoon years waves 1 and 2 are greater source of energy to other waves via both wave-wave interactions and wave to zonal mean flow interactions during monsoon months in the upper troposphere.